A method for detecting local selective corrosion of stainless steel

Through electrochemical methods, open-circuit voltage and cyclic polarization electrochemical tests were carried out on stainless steel, combined with micromorphic observation, the problem of indistinguishable local selection corrosion evaluation of super stainless steel was solved, quantitative analysis and distinction were achieved, and the accuracy of detection was improved. Security.

CN118794874BActive Publication Date: 2025-02-07NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411266477.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-02-07
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The local selection of super stainless steel is difficult to distinguish. The traditional method is very dangerous and cumbersome in the post-processing. The ordinary stainless steel method cannot adapt to super stainless steel.

Method used

Using electrochemical methods, by immersing stainless steel in a specific electrolyte for open circuit voltage testing and cyclic polarization electrochemical testing, the ratio of the second current peak to the first current peak is calculated to corrode characterization parameter IG, and combine it with micromorphology. Observe to distinguish.

Benefits of technology

Quantitative analysis and distinction of locally selected corrosion degree of stainless steel is achieved, and the accuracy and safety of detection are improved. It is suitable for super stainless steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118794874B_ABST
    Figure CN118794874B_ABST
Patent Text Reader

Abstract

The present invention provides a method for detecting local selective corrosion of stainless steel, and belongs to the technical field of material corrosion resistance evaluation. The present invention immerses stainless steel in an electrolyte, selects a suitable electrolyte formula, wherein sulfuric acid and hydrochloric acid are used to dissolve metal grain boundaries, which is beneficial to subsequent electrochemical testing, uses potassium thiocyanate as a depolarizing agent for electrochemical testing, and selects a suitable scanning rate to obtain a corrosion characterization parameter I G , and then combined with the microscopic morphology of stainless steel, multiple stainless steel samples can be distinguished, thereby accurately and quantitatively evaluating the degree of local selective corrosion. The experimental results show that the detection method provided by the present invention can detect the four samples I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material corrosion resistance evaluation, and in particular relates to a method for detecting local selective corrosion of stainless steel. Background Art

[0002] As a material with excellent corrosion resistance and high strength, super stainless steel has been widely used in the field of new energy. First of all, super stainless steel is widely used in photovoltaic brackets, solar water heaters and other equipment in the field of solar energy. Due to its antioxidant properties and high strength characteristics, it is not easy to rust in long-term outdoor use, which can ensure the long-term and stable operation of photovoltaic equipment; in the field of wind energy, super stainless steel helps to improve the stability and corrosion resistance of the entire system, thereby extending the service life of wind turbines. In addition, super stainless steel is lighter than other materials, which helps to reduce the weight of wind power generation equipment and improve the efficiency and operation stability of wind power generation; in the field of energy storage equipment, new energy-related energy storage equipment requires higher corrosion resistance and safety performance. Super stainless steel plays an important role in the manufacture of energy storage equipment due to its strong corrosion resistance and low-temperature toughness; the manufacture of new energy vehicles is another important application field of super stainless steel. Super stainless steel can be used in the manufacture of new energy vehicle bodies, motor components, high-temperature components, etc. These parts require materials with high corrosion resistance and high strength characteristics to make the manufacture of new energy vehicles more efficient and environmentally friendly; fuel cells are one of the most rapidly developing new energy technologies in recent years, and super stainless steel is also widely used in this field. For example, the development and application of TISCO's super ultra-pure ferritic stainless steel TFC22-X solves the problem of key strategic materials in the fuel cell industry.

[0003] In summary, due to its unique physical and chemical properties, super stainless steel has a broad application prospect in the field of new energy. With the continuous development and innovation of the new energy industry, super stainless steel is expected to play a more important role in the future.

[0004] However, the local selective corrosion evaluation of super stainless steel has always been a difficult problem, because the corrosion resistance of super stainless steel is very strong. Even if its corrosion resistance is weakened under high-temperature heat treatment conditions, the distinction between samples is small. Traditional evaluation methods such as acid solution immersion method are difficult to distinguish between series of samples, and the immersion time cycle is long, the experimental temperature is high, the risk is high, and the post-processing is cumbersome. In addition, the local selective corrosion method of ordinary stainless steel cannot be adapted to super stainless steel, which is attributed to the different sensitivity of the corrosive medium to different steel grades.

[0005] The electrochemical method is one of the effective methods for evaluating the local selective corrosion of stainless steel, but it is rarely used in the field of super stainless steel, and there is no perfect standard to regulate it. At the same time, super stainless steel has very high requirements for local corrosion media, which requires the test system to accurately distinguish the slight differences between different samples. Therefore, how to use electrochemical methods to distinguish the degree of local selective corrosion of a series of samples has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0006] The purpose of the present invention is to provide a method for detecting local selective corrosion of stainless steel. The detection method provided by the present invention can quantitatively analyze the degree of local selective corrosion and distinguish a series of samples.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for detecting local selective corrosion of stainless steel, comprising the following steps:

[0009] (1) immersing a plurality of stainless steels in an electrolyte respectively, performing an open circuit voltage test, and obtaining a stable open circuit voltage; the electrolyte comprises 2.2-2.8 mol / L sulfuric acid, 1.1-1.4 mol / L hydrochloric acid, 0.008-0.012 mol / L potassium thiocyanate, and water;

[0010] (2) performing cyclic polarization electrochemical tests on the plurality of stainless steels in step (1) to obtain a first current peak I1 and a second current peak I2; the scanning rate of the cyclic polarization electrochemical test is 1.5 mV / s;

[0011] (3) Calculate the ratio of the second current peak I2 obtained in step (2) to the first current peak I1 to obtain the corrosion characterization parameter I G ;

[0012] (4) Observe the microscopic morphology of multiple stainless steels after the cyclic polarization electrochemical test in step (2), and combine the corrosion characterization parameter I obtained in step (3) G Make a distinction.

[0013] Preferably, the stainless steel in step (1) is super stainless steel 27Cr-7Ni.

[0014] Preferably, the electrolyte in step (1) comprises 2.5-2.6 mol / L sulfuric acid, 1.2-1.3 mol / L hydrochloric acid, 0.009-0.01 mol / L potassium thiocyanate and water.

[0015] Preferably, the electrolyte in step (1) is 2.5 mol / L sulfuric acid, 1.2 mol / L hydrochloric acid, 0.01 mol / L potassium thiocyanate and water.

[0016] Preferably, the open circuit voltage test time in step (1) is 400s.

[0017] Preferably, the temperature during the open circuit voltage test in step (1) is 23-27°C.

[0018] Preferably, the temperature during the open circuit voltage test in step (1) is 25°C.

[0019] Preferably, the potential of the cyclic polarization electrochemical test in step (2) is -0.5V~0.4V.

[0020] Preferably, the cyclic polarization electrochemical test in step (2) adopts a three-electrode system, wherein the working electrode of the three-electrode system is stainless steel, the reference electrode is a solid electrode, and the counter electrode is a platinum electrode.

[0021] The invention provides a method for detecting local selective corrosion of stainless steel, comprising the following steps: immersing a plurality of stainless steels in an electrolyte respectively, performing an open circuit voltage test, and obtaining a stable open circuit voltage; the electrolyte comprises 2.2-2.8 mol / L sulfuric acid, 1.1-1.4 mol / L hydrochloric acid, 0.008-0.012 mol / L potassium thiocyanate and water; performing a cyclic polarization electrochemical test on the plurality of stainless steels respectively, and obtaining a first current peak I1 and a second current peak I2; the scanning rate of the cyclic polarization electrochemical test is 1.5 mV / s; calculating the ratio of the second current peak I2 to the first current peak I1, and obtaining a corrosion characterization parameter I G ; The microscopic morphology of multiple stainless steels after the cyclic polarization electrochemical test was observed, combined with the corrosion characterization parameter I G The present invention immerses stainless steel in an electrolyte, selects a suitable electrolyte formula, wherein sulfuric acid and hydrochloric acid are used to dissolve the metal grain boundaries, which is beneficial to subsequent electrochemical testing, uses potassium thiocyanate as a depolarizing agent for electrochemical testing, and selects a suitable scanning rate to obtain the corrosion characterization parameter I G , and then combined with the microscopic morphology of stainless steel, multiple stainless steel samples can be distinguished, thereby accurately and quantitatively evaluating the degree of local selective corrosion. The experimental results show that the detection method provided by the present invention can detect the four samples I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the microscopic morphology of sample 1 after corrosion in comparative example 1;

[0023] Figure 2 This is the microscopic morphology of sample 2 after corrosion in comparative example 1;

[0024] Figure 3 This is the microscopic morphology of sample 3 after corrosion in comparative example 1;

[0025] Figure 4 This is the microscopic morphology of sample 4 after corrosion in comparative example 1;

[0026] Figure 5 This is the microscopic morphology of sample 1 after corrosion in comparative example 4;

[0027] Figure 6 This is the microscopic morphology of sample 2 after corrosion in comparative example 4;

[0028] Figure 7 This is the microscopic morphology of sample 3 after corrosion in comparative example 4;

[0029] Figure 8 This is the microscopic morphology of sample 4 after corrosion in comparative example 4;

[0030] Fig. 9 This is the microscopic morphology of sample 1 after corrosion in Example 1;

[0031] Fig.10 This is the microscopic morphology of sample 2 after corrosion in Example 1;

[0032] Fig.11 This is the microscopic morphology of sample 3 after corrosion in Example 1;

[0033] Fig.12 This is the microscopic morphology of sample 4 after corrosion in Example 1. DETAILED DESCRIPTION

[0034] The present invention provides a method for detecting local selective corrosion of stainless steel, comprising the following steps:

[0035] (1) immersing a plurality of stainless steels in an electrolyte respectively, performing an open circuit voltage test, and obtaining a stable open circuit voltage; the electrolyte comprises 2.2-2.8 mol / L sulfuric acid, 1.1-1.4 mol / L hydrochloric acid, 0.008-0.012 mol / L potassium thiocyanate, and water;

[0036] (2) performing cyclic polarization electrochemical tests on the plurality of stainless steels in step (1) to obtain a first current peak I1 and a second current peak I2; the scanning rate of the cyclic polarization electrochemical test is 1.5 mV / s;

[0037] (3) Calculate the ratio of the second current peak I2 obtained in step (2) to the first current peak I1 to obtain the corrosion characterization parameter I G ;

[0038] (4) Observe the microscopic morphology of multiple stainless steels after the cyclic polarization electrochemical test in step (2), and combine the corrosion characterization parameter I obtained in step (3) G Make a distinction.

[0039] The detection method provided by the present invention is applicable to stainless steel, preferably to super stainless steel 27Cr-7Ni, and more preferably to super stainless steel 27Cr-7Ni treated at high temperature. The present invention has no special limitation on the process parameters of the high temperature treatment, and they can be adjusted as needed.

[0040] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0041] The present invention immerses a plurality of stainless steels into electrolyte respectively, performs an open circuit voltage test, and obtains a stable open circuit voltage.

[0042] In the present invention, the number of the stainless steel is preferably four.

[0043] The present invention has no special limitation on the size of the stainless steel, which can be adjusted according to actual needs.

[0044] In the present invention, the electrolyte comprises 2.2-2.8 mol / L sulfuric acid, 1.1-1.4 mol / L hydrochloric acid, 0.008-0.012 mol / L potassium thiocyanate and water, preferably comprises 2.5-2.6 mol / L sulfuric acid, 1.2-1.3 mol / L hydrochloric acid, 0.009-0.01 mol / L potassium thiocyanate and water, more preferably 2.5 mol / L sulfuric acid, 1.2 mol / L hydrochloric acid, 0.01 mol / L potassium thiocyanate and water. The present invention immerses a plurality of stainless steels in an electrolyte respectively, and selects a suitable electrolyte formula, wherein sulfuric acid and hydrochloric acid are used to dissolve metal grain boundaries, which is beneficial to subsequent electrochemical testing, and potassium thiocyanate is used as a depolarizing agent for electrochemical testing, so that the degree of local selective corrosion of the stainless steel can be accurately and quantitatively evaluated; by limiting the concentration of the electrolyte within the above range, the degree of local selective corrosion can be further accurately and quantitatively evaluated; and by limiting the electrolyte to 2.5 mol / L sulfuric acid, 1.2 mol / L hydrochloric acid, 0.01 mol / L potassium thiocyanate and water, the degree of local corrosion of a plurality of samples can be further distinguished.

[0045] The present invention has no particular limitation on the preparation method of the electrolyte, and any preparation method well known to those skilled in the art may be used.

[0046] The present invention has no particular limitation on the amount of the electrolyte, as long as the stainless steel is immersed in it.

[0047] The present invention has no particular limitation on the operation of immersing the stainless steel into the electrolyte, and the operation well known to those skilled in the art may be adopted.

[0048] In the present invention, the oxide film on the surface of the stainless steel is preferably removed before the open circuit voltage test.

[0049] The present invention preferably uses constant voltage cathodic polarization to remove the oxide film on the surface of stainless steel; the constant voltage is preferably -1.0~-1.4V, more preferably -1.2V; the time of the constant voltage cathodic polarization is preferably 12~17s, more preferably 15s.

[0050] In the present invention, the time of the open circuit voltage test is preferably 400s; the temperature during the open circuit voltage test is preferably 23-27°C, more preferably 25°C. The present invention can obtain a stable open circuit voltage by limiting the time of the open circuit voltage test within the above range; the present invention limits the temperature during the open circuit voltage test within the above range, and can obtain a stable grain boundary dissolution current value; setting the temperature to 25°C can further obtain a stable grain boundary dissolution current value.

[0051] After obtaining a stable open circuit voltage, the present invention performs cyclic polarization electrochemical tests on the plurality of stainless steels respectively to obtain a first current peak I1 and a second current peak I2.

[0052] In the present invention, the scanning rate of the cyclic polarization electrochemical test is 1.5 mV / s. The present invention selects a suitable scanning rate to accurately detect the local selective corrosion of stainless steel, thereby accurately and quantitatively evaluating the degree of local selective corrosion.

[0053] In the present invention, the potential of the cyclic polarization electrochemical test is preferably -0.5V~0.4V; the cyclic polarization electrochemical test preferably adopts a three-electrode system; the working electrode of the three-electrode system is preferably stainless steel; the reference electrode of the three-electrode system is preferably a solid electrode; the counter electrode of the three-electrode system is preferably a platinum electrode. The present invention has no special restrictions on the specific connection method and size of the three-electrode system, and a three-electrode system well known to those skilled in the art can be used.

[0054] In the present invention, the cyclic polarization electrochemical test preferably comprises the following steps:

[0055] 1) From -0.5V SCE Start by scanning forward to +0.4V SCE , and obtain the first current peak I1;

[0056] 2) Continue the cyclic polarization electrochemical test and obtain the second current peak I2.

[0057] The present invention preferably starts from -0.5V SCEStart by scanning forward to +0.4V SCE , and obtain the first current peak I1.

[0058] The present invention is effective for -0.5V SCE Start by scanning forward to +0.4V SCE There is no special limitation on the operation of obtaining the first current peak I1, and any operation well known to those skilled in the art may be used.

[0059] After obtaining the first current peak I1, the present invention preferably continues the cyclic polarization electrochemical test to obtain the second current peak I2.

[0060] The present invention has no special limitation on the operation of continuing the cyclic polarization electrochemical test to obtain the second current peak I2, and the operation well known to those skilled in the art can be adopted.

[0061] After obtaining the first current peak I1 and the second current peak I2, the present invention calculates the ratio of the second current peak I2 to the first current peak I1 to obtain the corrosion characterization parameter I G The present invention uses corrosion characterization parameters to distinguish various samples, that is, when the corrosion characterization parameters differ greatly, various samples can be distinguished.

[0062] The present invention has no special limitation on the phase difference value of the corrosion characterization parameter, and the phase difference values ​​of the corrosion characterization parameters of a series of samples can be large.

[0063] Get the corrosion characterization parameter I G After that, the present invention conducts microscopic morphology observation on a plurality of stainless steels after the cyclic polarization electrochemical test is completed, and combines the corrosion characterization parameter I G Make a distinction.

[0064] The present invention performs microscopic morphology observation on the stainless steel obtained by the cyclic polarization electrochemical test and distinguishes the stainless steel by combining corrosion characterization parameters without any special limitation, and the operation well known to those skilled in the art can be adopted.

[0065] The detection method provided by the present invention has the advantages of high repetition rate, high detection sensitivity, and easy operation. These advantages are derived from the precise selection of electrolyte and the fine control of electrochemical test parameters. Under these combined conditions, accurate detection of local selective corrosion of stainless steel can be obtained.

[0066] The detection method provided by the present invention is applicable to super stainless steel 27Cr-7Ni, and can accurately and quantitatively evaluate the degree of local selective corrosion in a high temperature environment, and can observe the process of local selective corrosion of 27Cr-7Ni from none to slight to severe; by I G The value can quantitatively analyze the degree of local selective corrosion, including the slight differences between samples, and has a high reproducibility.

[0067] The I in the cyclic polarization electrochemical test method G The value combined with the corrosion morphology observation can determine the effectiveness and reliability of the detection method provided by the present invention.

[0068] Reasonable electrolyte formula and selection of electrochemical parameters are the key points of the present invention. The optimal formula combination is finally obtained through experimental testing and morphology observation to obtain a local selective corrosion detection method for super stainless steel 27Cr-7Ni.

[0069] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0070] The raw materials used in the embodiments and comparative examples are 27Cr-7Ni, source: Shanghai Baowu Group, and the samples are square specimens of 1.2×1.2×1.2 cm; the experimental objects are: sample 1 is a 27Cr-7Ni blank sample, sample 2 is 27Cr-7Ni treated at 800°C for 30 min, sample 3 is 27Cr-7Ni treated at 800°C for 1 h, and sample 4 is 27Cr-7Ni treated at 800°C for 24 h; open circuit potential and cyclic polarization electrochemical tests are carried out using a CHI 600E electrochemical workstation; the cyclic polarization electrochemical test adopts a three-electrode system; the working electrodes of the three-electrode system are 4 samples; the reference electrode of the three-electrode system is a saturated calomel electrode (SCE); the counter electrode of the three-electrode system is a platinum electrode.

[0071] Comparative Example 1

[0072] The four samples were immersed in an aqueous solution of 2 mol / L sulfuric acid + 1 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 20°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G, respectively: sample 1: 2.2%, sample 2: 7.6%, sample 3: 7.8%, sample 4: 8.6%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed, and 4 groups of morphologies were obtained as follows Figures 1 to 4 As shown, the corrosion characterization parameters are then combined for observation.

[0073] Figure 1 This is the microscopic morphology of sample 1 after corrosion in comparative example 1; Figure 2 This is the microscopic morphology of sample 2 after corrosion in comparative example 1; Figure 3 This is the microscopic morphology of sample 3 after corrosion in comparative example 1; Figure 4 This is the microscopic morphology of sample 4 after corrosion in comparative example 1.

[0074] Depend on Figures 1 to 4 Combined 4 samples of I G It can be seen that the I G The values ​​are too close, the morphologies are similar, and the corrosion is slight; the four samples cannot be identified and distinguished.

[0075] Comparative Example 2

[0076] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 20°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 3.1%, Sample 2: 8.2%, Sample 3: 8.6%, Sample 4: 9.3%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0077] Combined 4 samples of I G From the morphology, it can be seen that the I G The values ​​are too close, the morphologies are similar, and the corrosion is slight; the four samples cannot be identified and distinguished.

[0078] By comparing Comparative Example 1 with Comparative Example 2, it can be seen that when the sulfuric acid concentration is set to 2.5 mol / L, the I GThe difference is gradually widening, but it is still indistinguishable.

[0079] Comparative Example 3

[0080] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 20°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 4.3%, Sample 2: 9.1%, Sample 3: 9.8%, Sample 4: 10.2%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0081] Combined 4 samples of I G From the morphology, it can be seen that the I G The values ​​are too close, the morphologies are similar, and the corrosion is slight; the four samples cannot be identified and distinguished.

[0082] By comparing Comparative Example 2 with Comparative Example 3, it can be seen that when the hydrochloric acid concentration is set to 1.2 mol / L, the I G The difference is gradually widening, but it is still indistinguishable.

[0083] Comparative Example 4

[0084] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 2mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G, respectively: sample 1: 5.2%, sample 2: 76.5%, sample 3: 78.7%, sample 4: 84.3%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed, and 4 groups of morphologies were obtained as follows Figures 5 to 8 As shown, the corrosion characterization parameters are then combined for observation.

[0085] Figure 5 This is the microscopic morphology of sample 1 after corrosion in comparative example 4; Figure 6 This is the microscopic morphology of sample 2 after corrosion in comparative example 4; Figure 7 This is the microscopic morphology of sample 3 after corrosion in comparative example 4; Figure 8 This is the microscopic morphology of sample 4 after corrosion in comparative example 4.

[0086] Depend on Figures 5 to 8 Combined 4 samples of I G It can be seen that the I G The values ​​are too close, the morphologies are similar, and the corrosion is severe; the four samples cannot be identified or distinguished.

[0087] Comparison of Comparative Example 3 and Comparative Example 4 shows that when the temperature is set to 25°C and the scanning rate is set to 2mV / s, the I G The difference is gradually widening, but it is still indistinguishable.

[0088] Example 1

[0089] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1.5mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: sample 1: 4.7%, sample 2: 9.3%, sample 3: 17.6%, sample 4: 26.4%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed, and 4 groups of morphologies were obtained as follows Figures 9 to 12 As shown, the corrosion characterization parameters are then combined for observation.

[0090] Fig. 9 This is the microscopic morphology of sample 1 after corrosion in Example 1; Fig.10 This is the microscopic morphology of sample 2 after corrosion in Example 1; Fig.11 This is the microscopic morphology of sample 3 after corrosion in Example 1; Fig.12 This is the microscopic morphology of sample 4 after corrosion in Example 1.

[0091] Depend on Figures 9 to 12 Combined 4 samples of I G It can be seen that the I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.

[0092] By comparing Comparative Example 4 with Example 1, it can be seen that when the scan rate is set to 1.5 mV / s, the I G The difference is large and the morphology is different, so they can be distinguished.

[0093] Example 2

[0094] The four samples were immersed in an aqueous solution of 2.2 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1.5mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 4.5%, Sample 2: 9.0%, Sample 3: 17.4%, Sample 4: 26.0%; then the stainless steel obtained by the cyclic polarization electrochemical test was subjected to microscopic morphology observation to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0095] Combined 4 samples of I G From the morphology, we can see that the I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.

[0096] Example 3

[0097] The four samples were immersed in an aqueous solution of 2.8 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCEThe surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1.5mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 5.3%, Sample 2: 10.2%, Sample 3: 18.1%, Sample 4: 27.2%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0098] Combined 4 samples of I G From the morphology, we can see that the I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.

[0099] Example 4

[0100] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.1 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1.5mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 4.5%, Sample 2: 9.1%, Sample 3: 17.4%, Sample 4: 26.0%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0101] Combined 4 samples of I G From the morphology, we can see that the I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.

[0102] Example 5

[0103] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.4 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1.5mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 5.0%, Sample 2: 9.5%, Sample 3: 17.9%, Sample 4: 26.7%; then the stainless steel obtained by the cyclic polarization electrochemical test was subjected to microscopic morphology observation to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0104] Combined 4 samples of I G From the morphology, we can see that the I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.

[0105] Example 6

[0106] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.008 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1.5mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 4.6%, Sample 2: 9.2%, Sample 3: 17.4%, Sample 4: 26.3%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0107] Combined 4 samples of I G From the morphology, we can see that the I GThe value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.

[0108] Example 7

[0109] The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.012 mol / L potassium thiocyanate at 25°C and subjected to a three-electrode electrochemical test: First, a -1.2 V SCE The surface film was removed by constant voltage cathodic polarization for 15 s, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, a cyclic polarization test was performed from -0.5 V SCE Start by scanning forward to +0.4V SCE , the scanning rate is set to 1.5mV / s, the first current peak I1 is obtained, and the cyclic polarization electrochemical test is continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 is calculated to obtain 4 sets of corrosion characterization parameters I G , respectively: Sample 1: 4.8%, Sample 2: 9.4%, Sample 3: 17.8%, Sample 4: 26.6%; then the stainless steel obtained by the cyclic polarization electrochemical test was subjected to microscopic morphology observation to obtain 4 groups of morphologies, which were then observed in combination with corrosion characterization parameters.

[0110] Combined 4 samples of I G From the morphology, we can see that the I G The value distinction is large and the morphology is different, which can be used to describe the degree of local selective corrosion.

[0111] It can be seen from the above embodiments and comparative examples that the detection method provided by the present invention can quantitatively analyze the degree of local selective corrosion and distinguish a series of samples.

[0112] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for detecting local selective corrosion of stainless steel, comprising the following steps; The four samples were immersed in an aqueous solution of 2.5 mol / L sulfuric acid + 1.2 mol / L hydrochloric acid + 0.01 mol / L potassium thiocyanate, and three-electrode electrochemical tests were performed at 25 °C: first, -1.2VSCE constant voltage cathodic polarization was performed for 15 s to remove the surface film, and then an open circuit potential test was performed for 400 s to obtain a stable open circuit voltage. Finally, the cyclic polarization test started from -0.5VSCE and scanned forward to +0.4VSCE. The scan rate was set to 1.5 mV / s to obtain the first current peak I1. The cyclic polarization electrochemical test was continued to obtain the second current peak I2. The ratio of the second current peak I2 to the first current peak I1 was calculated to obtain 4 groups of corrosion characterization parameters I G , respectively: Sample 1: 4.7%, Sample 2: 9.3%, Sample 3: 17.6%, Sample 4: 26.4%; then the microscopic morphology of the stainless steel obtained by the cyclic polarization electrochemical test was observed, and then observed in combination with the corrosion characterization parameters; The stainless steel is 27Cr-7Ni; The experimental objects are: sample 1 is a 27Cr-7Ni blank sample, sample 2 is 27Cr-7Ni treated at 800℃ for 30min, sample 3 is 27Cr-7Ni treated at 800℃ for 1h, and sample 4 is 27Cr-7Ni treated at 800℃ for 24h; Open circuit potential and cyclic polarization electrochemical tests were performed using a CHI 600E electrochemical workstation; The cyclic polarization electrochemical test adopts a three-electrode system; the working electrodes of the three-electrode system are 4 samples; the reference electrode of the three-electrode system is a saturated calomel electrode; and the counter electrode of the three-electrode system is a platinum electrode.